A quantum wave packet study of three-dimensional inelastic scattering - Gogtas, F; Bulut, N (Taylor & Francis Ltd, 2002)
A time-dependent quantum mechanical method has been described to calculate the state-to-state inelastic scattering probabilities for three-dimensional atom-diatom inelastic scattering at the zero total angular momentum. The method utilizes the potentially optimized discrete variable representation (DVR) technique for operating a diatomic Hamiltonian on the wave function and avoids the necessity of repeating many Fourier transformations for this operation. The method has been applied to the He + H-2(v,j) --> He + H-2(v',j') inelastic scattering problem.
Keywords: Reactive Scattering; Molecular Photofragmentation; Schrodinger-Equation; Dynamics; Probabilities; Collisions; Ho2